2022
DOI: 10.1371/journal.pone.0276270
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing intentions, fertility awareness knowledge and contraceptive use among female university students in Cameroon

Abstract: Objectives The primary objective of this study was to examine the association between fertility awareness knowledge, and contraceptive use among sexually active female university students (FUS) in Cameroon. Methods This study was designed as a secondary data analysis of a cross-sectional survey that was conducted between July and August 2018. We extracted and analyzed relevant data (i.e., socio-demographic characteristics, sexual behavior, fertility-related characteristics, and contraceptive use) using a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
0
1
Order By: Relevance
“…30 The findings of this study revealed that respondents have a high degree of knowledge regarding age and pregnancy, with around 83.5% of them correctly answering the question, "At what age is it easier to become pregnant?" This finding can be considered inconsistent with the results of some previous studies [31][32][33] and similar to the results of some other studies. 34 Probably, the high level of knowledge among…”
Section: Discussioncontrasting
confidence: 95%
“…30 The findings of this study revealed that respondents have a high degree of knowledge regarding age and pregnancy, with around 83.5% of them correctly answering the question, "At what age is it easier to become pregnant?" This finding can be considered inconsistent with the results of some previous studies [31][32][33] and similar to the results of some other studies. 34 Probably, the high level of knowledge among…”
Section: Discussioncontrasting
confidence: 95%
“…This meta-analysis shows that women who have multiple sexual partners are more likely to have repeat-induced abortions. This is in line with the study done in Cambodia [ 57 ] and the USA [ 58 ]. The possible explanation is that having multiple sexual partners will expose a woman to unstable relationships and several sexual episodes in sex, which leads to irregular use of contraceptives and unintended pregnancy, and subsequent abortion [ [19] , [57] , [59] ,].…”
Section: Discussionsupporting
confidence: 92%
“…Chan et al (9) reported that having a stable partner to share responsibilities with is crucial in childbearing decisions. Söderberg et al (18) found that women with a partner had more positive attitudes in the future importance of childbearing and female identity subscales. In many studies, it was also reported that engaged and married female students had more positive attitudes towards parenthood and childbearing, (19) and that not finding the right partner, (9) having a partner with common characteristics, (28) having a stable relationship, and sharing responsibilities with the partner, were important in the decision to become a parent.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Another study in female university students in Cameroon, showed that most of the female students intend to have children in the future, but their fertility awareness knowledge was suboptimal. (18) Considering the fact that a deeper understanding of the attitudes towards fertility and motherhood may help clarify the decision to have children among young individuals in Turkish young females, there is a great need for further study in this area. Therefore the current study aimed to determine the attitude towards fertility and childbearing in female university students…”
Section: Introductionmentioning
confidence: 99%